2021
DOI: 10.1016/j.heliyon.2021.e06308
|View full text |Cite
|
Sign up to set email alerts
|

Water use efficiency, grain yield, and economic benefits of common beans (Phaseolus vulgaris L.) under four soil tillage systems in Mukono District, Uganda

Abstract: With the increasing climate change impacts and variabilities, water is becoming a limiting factor for rainfed crop production in Uganda. Conservation tillage practices could improve soil and water conservation in croplands. Field experiments were conducted for three consecutive seasons from April 2019 to June 2020. The experiments evaluated the effect of soil tillage treatments on soil water storage, water use efficiency, grain yield, and economic benefits of the common beans (Phaseolus vulgaris L.) in two sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…According to these researchers, the higher yield in the no-tillage system may be due to the greater roots colonization by arbuscular mycorrhizal fungi (AMF). Similarly, Fatumah et al [169] observed that seed yield of common bean crop was approximately 45% higher in NT, and stubble-mulching tillage systems compared to CT and grain water use efficiency was about 56-83% higher under these two tillage systems compared to the CT system. The age of a no-tillage system is also an important factor, and in experiments conducted in Brazil over 23 years of an established NT system, Soratto et al [170] observed that both seed yield (1786 kg ha −1 ) and crude protein content (226 g kg −1 ) were higher compared to a newly established NT.…”
Section: Tillagementioning
confidence: 84%
“…According to these researchers, the higher yield in the no-tillage system may be due to the greater roots colonization by arbuscular mycorrhizal fungi (AMF). Similarly, Fatumah et al [169] observed that seed yield of common bean crop was approximately 45% higher in NT, and stubble-mulching tillage systems compared to CT and grain water use efficiency was about 56-83% higher under these two tillage systems compared to the CT system. The age of a no-tillage system is also an important factor, and in experiments conducted in Brazil over 23 years of an established NT system, Soratto et al [170] observed that both seed yield (1786 kg ha −1 ) and crude protein content (226 g kg −1 ) were higher compared to a newly established NT.…”
Section: Tillagementioning
confidence: 84%
“…In the common beans field of Uganda, NT and stubble-mulching improved soil water storage by 46 and 45%, respectively [123], compared with CT in the 0-100 cm soil depth over 14 months. In the study of long-term maize production mode, the NT ↔ ST treatment showed a good water storage effect [96].…”
Section: Effects On Soil Moisturementioning
confidence: 92%
“…Compared with CT, NT ↔ ST significantly increased crop yield and WUE in continuous cropping fields of corn. In the common bean fields of Uganda, NT and stubble mulching improved WUE and grain yield [123].…”
Section: Effects On Pests/natural Enemiesmentioning
confidence: 93%
See 1 more Smart Citation
“…This might be another reason that deep tillage did not always increase crop production under dry conditions. In arid areas, no-till preserves more soil moisture and achieves relatively higher crop yields [53]. Therefore, the selection of a tillage system requires consideration of soil characteristics, climate, and water supply conditions.…”
Section: Crops Response To Different Tillage Practicesmentioning
confidence: 99%